Soil pore structure and its research methods: A review - Wang, Nannan; Zhang, Tibin (Soil and water research, 2024)
Soil pore is an important part of soil structure. According to the causes of formation, soil pores can be divided into biological pores formed by animal movement and plant root development and non-biological pores formed by dry-wet and freeze-thaw alternation or artificial tillage. The soil pore structure affects the migration of water, gas, nutrients and so on in the soil, especially the macropores can also produce water or solute preferential migration. Studying soil pores is of great significance for predicting soil hydraulic properties, reducing groundwater pollution and soil nutrient loss. Based on previous studies on soil pore structure, this paper systematically summarized the role of soil pores, influencing factors and the advantages and disadvantages of various research methods. This paper not only introduces traditional methods (including direct and indirect methods), but also summarizes the new research on soil pores combined with computed tomography (CT) technology and other science and technology in recent years. Finally, the prospect and development trend of soil pore research in the future were predicted, so as to provide reference for further research on soil pore structure.